Adaptation and validation of a brief DSM-5 based psychiatric rating scale for childhood and adolescent mental health in Uganda: the Child and Adolescent Symptom Inventory-Progress Monitor (CASI-PM). Issue 2 (2nd April 2020) - Mpango, Richard Stephen; Ssembajjwe, Wilber; Muyingo, Sylvia Kiwuwa; Gadow, Kenneth D.; Patel, Vikram; Kinyanda, Eugene
ABSTRACT: We describe the process of locally adapting and validating the international psychiatric symptom screening instrument, the Child and Adolescent Symptom Inventory-Progress Monitor-parent version (CASI-PM-P) for use among youth in the sub-Saharan African setting of Uganda. To do this we used a methodology similar to that employed by the developers of this instrument. These analyses were undertaken among both a clinical sample (1, 339 HIV positive children and adolescents attending HIV care services in central and south-western Uganda) and a standardised sample (consisting of 323 HIV negative children and adolescents attending government schools in central Uganda). Pearson's correlations, Cronbach's alpha and analyses of variance were used to assess the reliability and validity of the adapted instrument. On item selection, 18 (64%) of the 28 psychiatric symptom items in the derived instrument showed large to moderate item-to-total minus item correlations. There was concordance on 17 (61%) of the psychiatric symptom items between the original version of the CASI-PM-P and the Uganda version. The selected psychiatric variable items in the derived version of the CASI-PM-P showed stability across age groups (children and adolescents), time (baseline and 6 months) and samples (clinical sample and standardised sample). The instrument showed good construct validity. In conclusion, the 29-item CASI-PM-P can, therefore, be used in the sub-Saharan African setting to screen for and monitor the progress of psychiatric symptoms among youth. However, the selection of the specific variable items to constitute a local version of the CASI-PM-P should be guided by local adaptation and validation studies.